2013
DOI: 10.1097/hjh.0b013e32835b0556
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein and later preeclampsia

Abstract: The pooled WMD suggest that women with higher levels of CRP may have an increased risk of developing preeclampsia. This association seems to be modified by confounders, such as BMI. Further studies of high methodological quality are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(37 citation statements)
references
References 56 publications
2
30
1
Order By: Relevance
“…The apparent discrepancy can be explained by differences in the timing of venipuncture, or methodological differences (including variation in study population and laboratory methods). The observation that CRP concentrations are higher in women with PE than in those with uncomplicated pregnancies at the time of diagnosis is consistent with previous studies (60, 149158), and may partly explain prior observations that patients with PE are at an increased risk of cardiovascular events in later life (102112). …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The apparent discrepancy can be explained by differences in the timing of venipuncture, or methodological differences (including variation in study population and laboratory methods). The observation that CRP concentrations are higher in women with PE than in those with uncomplicated pregnancies at the time of diagnosis is consistent with previous studies (60, 149158), and may partly explain prior observations that patients with PE are at an increased risk of cardiovascular events in later life (102112). …”
Section: Discussionsupporting
confidence: 90%
“…A solid body of evidence has shown that CRP is a major predictor of the subsequent risk of cardiovascular disease in non-pregnant subjects (135148). CRP is also known to be elevated in women with PE before (60, 149153) and at the time of diagnosis (154158). …”
Section: Introductionmentioning
confidence: 99%
“…The extent to which changes in this largely IL-6 and TNFα driven biomarker of inflammation are due to activation of classical innate immune responses or other cells (i.e. adipocytes or necrotic processes associated with placenta ageing) is under active investigation [83, 87, 88]. Interestingly, several groups have found undetectable changes or decreases in CRP over the course of healthy pregnancy [83, 8992].…”
Section: Discussionmentioning
confidence: 99%
“…Levels of CRP are significantly elevated in women who go on to develop preeclampsia compared to those who remain normotensive throughout pregnancy (14, 15). Additionally, variants in the CRP gene have been found to be associated with an increased risk for preeclampsia development (16, 17).…”
Section: Introductionmentioning
confidence: 99%